Porous Fe2O3 Nanorods on Hierarchical Porous Biomass Carbon as Advanced Anode for High-Energy-Density Asymmetric Supercapacitors - Yu, Pingping; Duan, Wei; Jiang, Yanfeng (Frontiers in Chemistry, 2020)
In this study, a novel negative electrode material was prepared by aligning α-Fe2O3 nanorods on a hierarchical porous carbon (HPC) skeleton. The skeleton was derived from wheat flours by a facile hydrothermal route to enhance conductivity, improve surface properties, and achieve substantially good electrochemical performances. The α-Fe2O3/HPC electrode exhibits enhanced specific capacitance of 706 F g-1, which is twice higher than that of α-Fe2O3. The advanced α-Fe2O3/HPC//PANI/HPC asymmetrical supercapacitor was built with an expanded voltage of 2.0 V in 1 M Li2SO4, possessing a specific capacitance of 212 F g-1 at 1 A g-1 and a maximum energy density of 117 Wh kg-1 at 1.0 kW kg-1, along with an excellent stability of 5.8% decay in capacitance after 5000 cycles. This study affords a simple process to develop asymmetric supercapacitors, which exhibit high electrochemical performances and are applicable in next-generation energy storage devices, based on α-Fe2O3 hybrid materials.